IN VITRO ANTI DIABETIC ACTIVITY OF MORINDA TINCTORIA FRUITS EXTRACTS - KUMARESAN, P.THIRUPATHY; SARAVANAN, S.; R.SUBISH (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate the glucose uptake of (antidiabetic activity) crude pet-ethe,benzene,chloroform,ethylacetate, ethanol,Â and methanol fruits extracts of Morinda tinctoria. Materials and Methods: Morinda tinctoria fruits extracts were subjected to inhibitory effect of glucose utilization using specific standard in vitro procedure. Results: The results in six different fruits extracts revealed that, the methanol extract at a concentration of 50 g plant extract/l was found to be more potent than other extracts with the lowest mean glucose concentration of 211+1.43 mg/dl at the end of 27 hrs. Conclusions: The present findings suggest that, the methanolic extract showed a significant inhibitory effect on glucose diffusion in vitro thus validating the traditional claim of the plant. Â Keywords: Antidiabetic activity, Glucose diffusion method, Morinda tinctoria